The Abe Doctrine Japan's Proactive Pacifism and Security Strategy - Akimoto, Daisuke (Springer Singapore, 2018)
This book focuses on Prime Minister Abe's policy toward international peace and security proposed in 2013 under the basic principle of 'proactive contribution to peace'. To this end, this book investigates Prime Minister Abe's policy-making process of the Peace and Security Legislation, which transformed Japan's security policy and enabled Japan to exercise the right of 'collective self-defense', which used to be 'unconstitutional'. This book evaluates the implications of the Peace and Security Legislation on three fronts, domestic, bilateral, and international, by analyzing Japan's Ballistic Missile Defense (BMD) program, the Japan-US alliance system, and Japan's policy on international peacekeeping operations in South Sudan. This book is one of the first contributions to the research on Japan's foreign and security policy under the Shinzo Abe administration and will be of interest to scholars, policymakers, and students of Japan, Japanese politics and international relations of the Asia-Pacific region.